2023
DOI: 10.3389/fnins.2023.1083928
|View full text |Cite
|
Sign up to set email alerts
|

Novel diagnostic biomarkers related to immune infiltration in Parkinson’s disease by bioinformatics analysis

Abstract: BackgroundParkinson’s disease (PD) is Pengfei Zhang Liwen Zhao Pengfei Zhang Liwen Zhao a common neurological disorder involving a complex relationship with immune infiltration. Therefore, we aimed to explore PD immune infiltration patterns and identify novel immune-related diagnostic biomarkers.Materials and methodsThree substantia nigra expression microarray datasets were integrated with elimination of batch effects. Differentially expressed genes (DEGs) were screened using the “limma” package, and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Neutrophils are of therapeutic interest because they are the most abundant circulating leukocyte in humans and have been shown in both human and mouse models to be associated with a worse prognosis in neurodegenerative diseases [7][8][9]. Genes involved in neutrophil activation and adhesion have been identified in areas with blood-brain barrier (BBB) disruption and associated with disease progression [10][11][12][13]. Furthermore, humanized AD mouse model studies have shown an increase in short-term spatial memory and a decrease in capillary blood flow stalling when targeting neutrophil adhesion or accumulation [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are of therapeutic interest because they are the most abundant circulating leukocyte in humans and have been shown in both human and mouse models to be associated with a worse prognosis in neurodegenerative diseases [7][8][9]. Genes involved in neutrophil activation and adhesion have been identified in areas with blood-brain barrier (BBB) disruption and associated with disease progression [10][11][12][13]. Furthermore, humanized AD mouse model studies have shown an increase in short-term spatial memory and a decrease in capillary blood flow stalling when targeting neutrophil adhesion or accumulation [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have correlated the onset and progression of neurodegenerative diseases with proin ammatory factors and immune cell activation and accumulation [7][8][9] . Transcriptomics studies have demonstrated an increase in pro-in ammatory differentially expressed genes (DEGs) in neurodegeneration, and genes involved in neutrophil activation and adhesion have been identi ed in areas with blood brain barrier (BBB) disruption and associated with disease progression 7,[9][10][11] . Neutrophils are of therapeutic interest because they are the most abundant circulating leukocyte and have been shown in both human and mouse models to be associated with a worse prognosis in neurodegenerative diseases [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%